PENGARUH MODAL SENDIRI DAN KREDIT USAHA RAKYAT (KUR) TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH DI KECAMATAN GOLEWA KABUPATEN NGADA - Wae, Maria Nestiana; Soleiman, Iriany Dewi; Reo, Hermanus (Jurnal Riset Ilmu Akuntansi, 2024)
In this study, the authors used a descriptive research type which is located on micro, small and medium enterprises (MSMEs) in Golewa District. The sample used was purposive sampling by setting a certain amount as a target that must be met because the research sample was known in advance, amounting to 74 people. In collecting data, this study used primary and secondary data, namely questionnaires for variable Y of this study, namely income for micro, small and medium enterprises (MSMEs) and for variables X Own Capital (X1), People's Business Credit (KUR) (X2). Data analysis using multiple linear regression analysis. The results of this study indicate that: (1) Own capital has a positive and significant influence on the income of micro, small and medium enterprises in Golewa sub-district, Ngada Regency, this is evidenced by the results of testing the coefficient value of the variable coefficient of own capital of 0.269 with t_count > t_table (3.467 > 1.993) and a significant level of 0.001 < 0.05, then HO is accepted. (2) People's business credit has a positive and significant effect on the income of micro, small and medium enterprises in Golewa sub-district, Ngada Regency, this is evidenced by the results of testing the coefficient value of the people's business credit variable coefficient of 0.206 with t_count > t_table (3.209 > 1.993) and a significant level 0.002 <0.05 then HO is accepted.